Potential for reducing emissions and carbon sequestration in forests and cocoa agroforestry systems in the Colombian Pacific - Mena-Mosquera, Víctor Eleazar (2021)
Introduction: Forests and agroforestry systems (AFS) provide ecosystem goods and services for society, such as climate change mitigation. Objective: The potential for emission reductions and carbon sequestration in forests and cocoa agroforestry systems in the Munguidó river sub-basin in Colombia was estimated. Methods: Three land use systems were selected (primary forest, secondary forest and AFS with cocoa). Eighteen temporary sampling plots were established, six per system, to measure trees (diameter at breast height -dbh ≥ 10 cm) and cocoa shrubs. Aboveground biomass was quantified with allometric equations and a carbon fraction of 0.5. Carbon fixation in secondary forest and AFS with cocoa was estimated as the ratio of carbon stored to its age. Carbon loss from primary forest was estimated based on deforestation for Chocó and that sub-basin (0.6 and 0.3 %/year, respectively). An analysis of variance and LSD Fisher mean comparison was performed to determine differences in carbon storage and carbon sequestration between uses. Results: Primary Forest stored more carbon than secondary forest and AFS with cocoa (190.1, 22.3 and 5.3 Mg/ha, respectively). The carbon fixation of secondary forest and AFS with cocoa did not differ (2.23 vs. 1.33 Mg/ha/year). In 20 years, the primary forest would present an emission reduction of 1.4-2.6 Tg CO2; and the secondary forest and the PFS with cocoa would present a sequestration of 100.8 and 30.7 Gg CO2, respectively. Conclusion: In the Munguidó river sub-basin, it is possible to establish projects for the reduction of emissions in primary forest and carbon sequestration in secondary forests and AFS with cocoa, which could emit 1.4-2.6 million tons of CO2.